2021
DOI: 10.48550/arxiv.2102.05175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transition space for the continuity of the Lyapunov exponent of quasiperiodic Schrödinger cocycles

Lingrui Ge,
Yiqian Wang,
Jiangong You
et al.

Abstract: We construct discontinuous point of the Lyapunov exponent of quasiperiodic Schrödinger cocycles in the Gevrey space G s with s > 2. In contrast, the Lyapunov exponent has been proved to be continuous in the Gevrey space G s with s < 2 [17,37]. This shows that G 2 is the transition space for the continuity of the Lyapunov exponent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Bourgain-Jitomirskaya [17] showed that the Lyapunov exponent L(α, A) : T × C ω (T, SL(2, C)) → R is jointly continuous for irrational α, and this result can be partially extended to ν-Gevrey topology with 1/2 < ν < 1. Recently, Ge-Wang-You-Zhao [27] showed that there exists a continuous-discontinuous transition for the Lyapunov exponent in the ν-Gevrey space at ν = 1/2.…”
Section: Introductionmentioning
confidence: 99%
“…Bourgain-Jitomirskaya [17] showed that the Lyapunov exponent L(α, A) : T × C ω (T, SL(2, C)) → R is jointly continuous for irrational α, and this result can be partially extended to ν-Gevrey topology with 1/2 < ν < 1. Recently, Ge-Wang-You-Zhao [27] showed that there exists a continuous-discontinuous transition for the Lyapunov exponent in the ν-Gevrey space at ν = 1/2.…”
Section: Introductionmentioning
confidence: 99%